2020
DOI: 10.1136/bmjopen-2020-041558
|View full text |Cite
|
Sign up to set email alerts
|

Effect of medicines management versus standard care on readmissions in multimorbid patients: a randomised controlled trial

Abstract: ObjectiveTo investigate the effect of pharmacist-led medicines management in multimorbid, hospitalised patients on long-term hospital readmissions and survival.DesignParallel-group, randomised controlled trial.SettingRecruitment from an internal medicine hospital ward in Oslo, Norway. Patients were enrolled consecutively from August 2014 to the predetermined target number of 400 patients. The last participant was enrolled March 2016. Follow-up until 31 December 2017, that is, 21–40 months.ParticipantsAcutely a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

9
29
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(41 citation statements)
references
References 45 publications
9
29
2
Order By: Relevance
“…The number and frequency of MRPs are also in line with previous Norwegian and Scandinavian studies, where MRPs have been identified in 80–100% of hospitalized internal medicines patients, 2,21,23,30 in the range of 2–9 MRPs per patient 2,22,24,30‐32 . The number and type of MRPs per patient vary across studies with similar interventions, 21,22,32,33 likely because of the lack of consensus concerning the classification of MRPs 34 . One outlier is the number of MRPs identified in a recently published study by Lea et al 21 They tested IMM working procedures in an intervention similar to IMMENSE and identified 3826 MRPs in 193 intervention patients giving a mean of 19.7 MRPs per patient 21 .…”
Section: Discussionsupporting
confidence: 86%
See 4 more Smart Citations
“…The number and frequency of MRPs are also in line with previous Norwegian and Scandinavian studies, where MRPs have been identified in 80–100% of hospitalized internal medicines patients, 2,21,23,30 in the range of 2–9 MRPs per patient 2,22,24,30‐32 . The number and type of MRPs per patient vary across studies with similar interventions, 21,22,32,33 likely because of the lack of consensus concerning the classification of MRPs 34 . One outlier is the number of MRPs identified in a recently published study by Lea et al 21 They tested IMM working procedures in an intervention similar to IMMENSE and identified 3826 MRPs in 193 intervention patients giving a mean of 19.7 MRPs per patient 21 .…”
Section: Discussionsupporting
confidence: 86%
“…For the single steps, all were delivered to over 80% of patients. An overall fidelity of 54.8% is in line with other studies showing fidelity of 53–67% of similar complex interventions, 20,21 while many studies do not report overall fidelity 9,10,22,23 …”
Section: Discussionsupporting
confidence: 84%
See 3 more Smart Citations